Time to wake up: No impact of COMT Val158Met gene variation on circadian preferences, arousal regulation and sleep. (8th August 2016) - Jawinski, Philippe; Tegelkamp, Sophie; Sander, Christian; Häntzsch, Madlen; Huang, Jue; Mauche, Nicole; Scholz, Markus; Spada, Janek; Ulke, Christine; Burkhardt, Ralph; Reif, Andreas; Hegerl, Ulrich; et al.
ABSTRACT: Dopamine has been implicated in the regulation of sleep–wake states and the circadian rhythm. However, there is no consensus on the impact of two established dopaminergic gene variants: the catechol-O-methyltransferase Val158Met (COMT Val158Met; rs4680) and the dopamine D4 receptor Exon III variable-number-of-tandem-repeat polymorphism (DRD4 VNTR). Pursuing a multi-method approach, we examined their potential effects on circadian preferences, arousal regulation and sleep. Subjects underwent a 7-day actigraphy assessment (SenseWear Pro3), a 20-minute resting EEG (analyzed using VIGALL 2.0) and a body mass index (BMI) assessment. Further, they completed the Morningness–Eveningness Questionnaire (MEQ), the Epworth Sleepiness Scale (ESS) and the Pittsburgh Sleep Quality Index (PSQI). The sample comprised 4625 subjects (19–82 years) genotyped for COMT Val158Met, and 689 elderly subjects (64–82 years) genotyped for DRD4 VNTR. The number of subjects varied across phenotypes. Power calculations revealed a minimum required phenotypic variance explained by genotype ranging between 0.5% and 1.5% for COMT Val158Met and between 3.3% and 6.0% for DRD4 VNTR. Analyses did not reveal significant genotype effects on MEQ, ESS, PSQI, BMI, actigraphy and EEG variables. Additionally, we found no compelling evidence in sex- and age-stratified subsamples. Few associations surpassed the threshold of nominal significance ( p < .05), providing some indication for a link between DRD4 VNTR and daytime sleepiness. Taken together, in light of the statistical power obtained in the present study, our data particularly suggest no impact of the COMT Val158Met polymorphism on circadian preferences, arousal regulation and sleep. The suggestive link between DRD4 VNTR and daytime sleepiness, on the other hand, might be worth investigation in a sample enriched with younger adults.